Preliminary investigation of polycationic polyurethane on ionic conductivity - Adam, Nurul Ilham; Su’ait, Mohd Sukor (2024)
This study investigates five types of polycationic Polyurethane (PU) with an emphasis on their ionic conductivity performance. These preliminary studies reveal that each of the polycationic PU shows promising electrochemical properties, indicating their potential suitability for advanced applications in energy storage systems and electronic devices. By examining different formulations and compositions, this research identifies key factors that influence ionic conductivity and overall performance. The initial findings suggest that these polycationic PUs could significantly enhance the efficiency and functionality of next-generation technologies. This foundational research lays the groundwork for more detailed studies, aiming to explore the full potential of polycationic PUs in high-performance applications, such as batteries, supercapacitors, and other electronic components.